Assessing the Awareness Level of COVID-19 in western Libyan cities (Journal of Medical Sciences, 2022)
Background:  The global spread of the COVID -19 epidemic was reflected in the region of East and North Africa, with dynamic, changing ups and downs at the regional level and directly threatening patients with chronic diseases, and comorbidities such as cardiovascular diseases, diabetes, respiratory diseases, and cancer. Objective: The purpose of this study was to determine the level of knowledge of COVID -19 in western Libyan cities. Methods: The use of (questionnaire) forms, assessing the health situation, awareness, and adherence to public health measures to control the COVID -19 epidemic for patients in the treatment of COVID -19. The study was conducted on an appropriate sample of volunteers in some Libyan cities (Gheryan, Zintan, Tajoura, Tripoli, Al-Zawiya, Surman, Sabratha, Al-Ajeilat, Al-Zawara & Al-Jamil). Results: The study was conducted on 1460 volunteers from Libyan cities. 400 of them are college students and 1,060 are people from the community. More than two-thirds of the volunteers (65.69%) are Female. The majority of the volunteers (79%) live in the cities. Most of the people infected with the virus suffer from mild to moderate respiratory illnesses. Although the number of cases of COVID -19 is currently increasing significantly, (69%) of the respondents have no or mild symptoms. (Most of the patients (90.0%) had refused to take the vaccine, (27%) had respiratory symptoms, and (17.2%) many had elevated D-dimer levels and inflammatory markers. Overall, 116 of the patients died (11.12%), and 260 (6.9%) had impaired health. Conclusion: The infection is also transmitted by people who are otherwise healthy and who are unaware of their illness.COVID-19 affects all people in different ways. Symptoms range from mild to moderate to severe and can lead to death, depending on the person's immunity and lifestyle. we recommend that the necessary precautions be taken to educate Libyan citizens; On the importance of steps that can be taken to reduce the likelihood of contracting COVID-19, reducing the possibility of transmission to others, and vaccination for coronavirus disease.